2017
DOI: 10.1149/2.0211713jes
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Model of Aluminum Behavior in Cement-Based Matrices Analyzed by Impedance Spectroscopy

Abstract: Aluminum reactivity in cement-based matrices, generally used for conditioning low-and intermediate-level radioactive wastes, is a problem due to dihydrogen produced by the corrosion reaction which depends on the pH of the pore solution. Electrochemical impedance spectroscopy has been used to propose a mechanism for aluminum corrosion in cementitious matrices based on ordinary Portland cement (OPC, pH ≈ 13) or magnesium phosphate cement (MKP, pH ranging between 4 and 9) containing or not LiNO 3 as a corrosion i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 41 publications
2
26
0
Order By: Relevance
“…Ordinary Portland cement (OPC) is one of the most widely used materials for conditioning radioactive wastes because it is inexpensive, it can easily be supplied and it exhibits high stability over time after hydration. [ 3 ] However, OPC possesses a high pH pore water solution. The natural oxide layer formed on the aluminium surface is amphoteric and, therefore, not resistant to corrosion when brought in contact with the highly alkaline cement pore water because the protected oxide film dissolves to form, for example, aluminium oxides and hydroxides, with the liberation of hydrogen gas.…”
Section: Introductionmentioning
confidence: 99%
“…Ordinary Portland cement (OPC) is one of the most widely used materials for conditioning radioactive wastes because it is inexpensive, it can easily be supplied and it exhibits high stability over time after hydration. [ 3 ] However, OPC possesses a high pH pore water solution. The natural oxide layer formed on the aluminium surface is amphoteric and, therefore, not resistant to corrosion when brought in contact with the highly alkaline cement pore water because the protected oxide film dissolves to form, for example, aluminium oxides and hydroxides, with the liberation of hydrogen gas.…”
Section: Introductionmentioning
confidence: 99%
“…The reactivity of Be has been studied using the same electrochemical approach that the one adopted previously to study the reactivity of Al and U encapsulated in a conditioning matrix: open circuit potential and electrochemical impedance spectroscopy measurements [44][45][46].…”
Section: Electrochemical Measurements Of Be In Conditioning Matricesmentioning
confidence: 99%
“…We have previously shown that cement brings an electrical contribution to the impedance measurement [45]. In order to discriminate the impedance related to the cement from the one related to the beryllium reactivity, measurements on a platinum electrode, as an inert electrode, have been performed in parallel.…”
Section: Eis Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aluminum acts as a reactive, amphoteric alloying element, which generates a protective oxide layer in the pH range 4-9 [63]. However, the oxide layer is unstable in acidic or alkaline solutions, therefore corrosion occurs with hydrogen gas evolution [64].…”
Section: Effect Of Al Alloying On High-mn Twip Steel Corrosionmentioning
confidence: 99%